2016
DOI: 10.1111/gcb.13214
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous genetic turnovers across Western Eurasia in Late Pleistocene collared lemmings

Abstract: Recent palaeogenetic studies indicate a highly dynamic history in collared lemmings (Dicrostonyx spp.), with several demographical changes linked to climatic fluctuations that took place during the last glaciation. At the western range margin of D. torquatus, these changes were characterized by a series of local extinctions and recolonizations. However, it is unclear whether this pattern represents a local phenomenon, possibly driven by ecological edge effects, or a global phenomenon that took place across lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 52 publications
9
54
0
Order By: Relevance
“…As such, for each glaciation that occurred, a substantial proportion of each species' lineage was lost, and with that its genetic heritage, complicating the interpretation of colonization patterns. The replacement of one phylogroup with another in line with climate oscillations has also been observed (Brace et al, 2012(Brace et al, , 2016Martínková et al, 2013;Palkopoulou et al, 2016;Searle et al, 2009) indicating that presentday genetic diversity alone can be insufficient to explain historical patterns (Hofreiter & Stewart, 2009;Searle et al, 2009). 2011;Stewart et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As such, for each glaciation that occurred, a substantial proportion of each species' lineage was lost, and with that its genetic heritage, complicating the interpretation of colonization patterns. The replacement of one phylogroup with another in line with climate oscillations has also been observed (Brace et al, 2012(Brace et al, , 2016Martínková et al, 2013;Palkopoulou et al, 2016;Searle et al, 2009) indicating that presentday genetic diversity alone can be insufficient to explain historical patterns (Hofreiter & Stewart, 2009;Searle et al, 2009). 2011;Stewart et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Using herbarium specimens to study evolution, population history, and invasion When drawing conclusions about the evolutionary history of species, inferences are (Palkopoulou et al, 2016;Leonardi et al, 2017). Modern distribution of alleles and genotypes can therefore differ significantly from the past distribution.…”
Section: Mining the Diversity Of Species Genomes Stored In Herbariamentioning
confidence: 99%
“…Interestingly, these results have often shown that local extinctions and population turnovers, rather than survival by habitat tracking, were the dominant processes during past climate warming (e.g. Dal en et al, 2007;Lagerholm et al, 2014;Palkopoulou et al, 2016). This raises concerns from a conservation perspective, as such local extinctions following habitat loss could lead to ensuing losses of unique genetic variation.…”
Section: Introductionmentioning
confidence: 99%